Can Auditors Improve Their Judgment by Drawing on the Crowd Within?† - Zimbelman, Aaron F. (Contemporary Accounting Research, 2022)
ABSTRACT This study examines whether auditors can improve their judgment by drawing on the crowd within—that is, making the same judgment twice and averaging the two responses. Improvements in judgment are of special interest to auditors given that poor judgment threatens audit effectiveness and efficiency. The results from my experiment suggest that drawing on the crowd within helps auditors better use their task‐relevant knowledge, leading to more accurate auditor judgments relative to the judgments of an expert panel. Also, auditors can employ different task‐relevant knowledge that leads to more justifiable judgments when they are prompted (vs. not prompted) to make a limited, intuitive initial judgment as they draw on the crowd within. Overall, auditors appear to increase their task‐relevant knowledge as they develop expertise but do not appear to better use that knowledge absent intervention. Auditors can manipulate how they draw on the crowd within to achieve different audit objectives—for example, accuracy versus justifiability.